The Prospects for Expansion and Cost-Effective Development of Mineral Resources in the Mining and Industrial Areas of India - Reddy Dhana Raju (Global Journal of Earth Science and Engineering, 2017)
Exploitation of different kinds of mineral deposits is currently addressed to recover mostly the main product from an ore, with little effort either for its co-/by-products or for value-addition and creation of wealth from waste. Presently, mineral industry is facing many problems that make it less attractive for old and new entrepreneurs. To overcome them, there is a need for ‘Mega-, Micro- and Nano (10-9)-Scale’ (MMNS) investigations on both working and potential ore deposits. Salient aspects of these multi-disciplinary and multi-faceted, both field- and laboratory-based, investigations, together with their main objectives, during different stages of ‘Mineral Exploration and Exploitation’ (MEE) are presented. Brief description of some major explored and exploited ore deposits in India, along with their possible, high-value by-products, and waste from a few mining industries, both recommended for research, are listed. Nano-scale mineral technology, presently in its initial stage, may be effectively used to isolate valuable elements or molecules from ore and gangue minerals as well as has the potentiality for ‘Recycling and Reusing’ (R & R) of waste material, thereby serving the twin concept of value-addition and creation of wealth from waste. Some pertinent problems of mineral industry, which can be tackled by comprehensive MMNS studies, and some requiring future Research and Development (R & D), as well as expected results of such research are given. The objectives of these studies on ore deposits are (i) maximum recovery of both the main and valuable co-/by-products from ores for value-addition, (ii) utilization of their waste material for creation of wealth from waste and (iii) expansion and cost-effective development of mineral resources in mining and industrial areas of India.